Divergent Isoprenoid Biosynthesis Pathways in Staphylococcus Species Constitute a Drug Target for Treating Infections in Companion Animals - Ana M. Misic (American Society for Microbiology, 2016)
ABSTRACT Staphylococcus species are a leading cause of skin and soft tissue infections in humans and animals, and the antibiotics used to treat these infections are often the same. Methicillin- and multidrug-resistant staphylococcal infections are becoming more common in human and veterinary medicine. From a “One Health” perspective, this overlap in antibiotic use and resistance raises concerns over the potential spread of antibiotic resistance genes. Whole-genome sequencing and comparative genomics analysis revealed that Staphylococcus species use divergent pathways to synthesize isoprenoids. Species frequently associated with skin and soft tissue infections in companion animals, including S. schleiferi and S. pseudintermedius, use the nonmevalonate pathway. In contrast, S. aureus, S. epidermidis, and S. lugdunensis use the mevalonate pathway. The antibiotic fosmidomycin, an inhibitor of the nonmevalonate pathway, was effective in killing canine clinical staphylococcal isolates but had no effect on the growth or survival of S. aureus and S. epidermidis. These data identify an essential metabolic pathway in Staphylococcus that differs among members of this genus and suggest that drugs such as fosmidomycin, which targets enzymes in the nonmevalonate pathway, may be an effective treatment for certain staphylococcal infections. IMPORTANCE Drug-resistant Staphylococcus species are a major concern in human and veterinary medicine. There is a need for new antibiotics that exhibit a selective effect in treating infections in companion and livestock animals and that would not be used to treat human bacterial infections. We have identified fosmidomycin as an antibiotic that selectively targets certain Staphylococcus species that are often encountered in skin infections in cats and dogs. These findings expand our understanding of Staphylococcus evolution and may have direct implications for treating staphylococcal infections in veterinary medicine.